Biological responses of Sri Lankan rice (Oryza sativa L.) varieties to rhythmic sound patterns (music and religious chants) - Sachithri Munasinghe; Shyama Weerakoon; Senaviratnege Somaratne (Smujo International, 2020)
Abstract. Munasinghe DSP, Weerakoon SR, Somaratne S. 2020. Biological responses of Sri Lankan rice (Oryza sativa L.) varieties to rhythmic sound patterns (music and religious chants). Nusantara Bioscience 12: 154-161. Influences of music cause either promoting or restricting the growth of plants. The effects of Pirith chanting and rhythmic sound patterns (Western classical music, Eastern classical music, Rock music) were focused in the present study. Seeds of Two (02) rice varieties (Bg 300 and Kuruluthuda) in f0 and f1 generations were subjected to dormancy break treatment, kept in a soundproof confined chamber, and arranged in Randomized Complete Block Design (RCBD) with two (02) replicates and 10 seeds per replicate. Seeds were germinated under the three sound rhythms, Pirith chanting, and silence. Plants kept under silence served as the control. Sound rhythms and Pirith were played separately for an hour, at 30 cm distance away from the seeds with an intensity of 55-60 dB for seven (07) days continuously, maintaining equal environmental conditions. Following seven (07) days, the percentile germination rate was recorded. Germinated seeds were planted in plastic pots filled with paddy soil, up to ¾ of the total depth, and pots were arranged in Randomized Complete Block Design (RCBD) with five (05) replicates and three (03) plants per replicate. Following one week, plants were subjected to sound rhythm treatments and silence for three (03) months continuously. Measurement of growth and yield performance were recorded every fortnight. Significantly different (p < 0.05) growth and yield performances in both generations were observed under Pirith, Eastern Classical and Western Classical music. Higher rates of growth were observed for rice varieties exposed to Pirith, Eastern and Western classical music. Similarly, yield was also higher compared to rice varieties exposed to rock music. The findings suggest that soft rhythmic sounds are the most appropriate type of music which improved growth and yield performance of rice varieties, Bg 300, and Kuruluthuda. However, further studies are needed to confirm present results and to elucidate the mechanism of responses to Pirith chanting and other rhythmic sound patterns using phytochemical and biochemical analyses.